Effects of organic matter in livestock manure digester liquid on microbial community structure and in situ activity of anammox granules. (September 2016) - Kindaichi, Tomonori; Awata, Takanori; Mugimoto, Yuichiro; Rathnayake, Rathnayake M.L.D.; Kasahara, Shinsuke; Satoh, Hisashi
Abstract: Anaerobic ammonium oxidation (anammox) is a promising process for NH4 + -rich wastewaters such as anaerobic digester liquids. In the present study, we investigated various properties of an up-flow column reactor containing anammox granules and fed with a real digester liquid at four different concentrations (Phases 1 to 4). The efficiencies of NH4 + and NO2 − removal decreased by up to 32% and 42%, respectively, in the digester-liquid-fed reactor (reactor-DL). When the performance of reactor-DL deteriorated, the community structure, spatial distribution, and in situ anammox activity in the two reactors were further investigated using 16S rRNA gene-based phylogenetic analysis, fluorescence in situ hybridization (FISH), and microelectrode measurements. The phylogenetic analysis and FISH results showed that non-anammox bacteria were predominant in the granule outer layers in reactor-DL, whereas anammox bacteria still dominated the granule interiors. Microelectrode measurements showed clear evidence of NH4 + oxidation activity in the interiors of granules from reactor-DL. Batch experiments using anammox granules at different acetate concentrations indicated that concentrations up to 50 mM had no effects on the anammox activity, whereas inorganic carbon uptake decreased in the presence of acetate. The present study clearly shows that the anammox activity and anammox bacterial density in the granules were maintained after feeding the digester liquid to the reactor for 140 days. Graphical abstract: Highlights: Digester liquids were fed to an anammox reactor. Anammox activity and bacterial density were lower in the outer layer of granules. Number of coexisting non-anammox bacteria increased in the outer layer of granules. Anammox activity in the inner part of the granules was maintained.